High-risk human papillomavirus in semen is associated with poor sperm progressive motility and a high sperm DNA fragmentation index in infertile men. Issue 2 (4th December 2018) - Boeri, Luca; Capogrosso, Paolo; Ventimiglia, Eugenio; Pederzoli, Filippo; Cazzaniga, Walter; Chierigo, Francesco; Pozzi, Edoardo; Clementi, Massimo; Viganò, Paola; Montanari, Emanuele; Montorsi, Francesco; Salonia, Andrea
Abstract: STUDY QUESTION: Does the presence of human papillomavirus (HPV) in semen impact seminal parameters and sperm DNA quality in white European men seeking medical help for primary couple's infertility? SUMMARY ANSWER: HPV seminal infections involving high-risk (HR) genotypes are associated with impaired sperm progressive motility and sperm DNA fragmentation (SDF) values. WHAT IS KNOWN ALREADY: HPV is commonly present in semen samples. However, whether the presence of HPV in semen is actually associated with impaired sperm parameters and SDF values have yet to be elucidated. STUDY DESIGN, SIZE, DURATION: In this cross-sectional study, complete demographic, clinical and laboratory data from 729 infertile men were analysed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Health-significant comorbidities were scored with the Charlson comorbidity index (CCI). Serum hormones and SDF index (measured by the sperm chromatin structure assay [SCSA]) were measured in every patient (SDF ≥30% was defined as pathological). Semen analysis was based on 2010 World Health Organisation reference criteria. Amplification by nested PCR was used to detect HPV-DNA sequences in semen samples. Descriptive statistics and linear regression models were used to test the association between the presence of HPV and clinical and seminal characteristics in the whole cohort. MAIN RESULTS AND THE ROLE OF CHANCE: The overall rate of HPV positivity was 15.5% (113/729). Overall, 78/729 (10.7%) and 35/729 (4.8%) patients had HR HPV+ and low-risk HPV+, respectively. HPV16 was the most prevalent type (22.1%), followed by HPV43 (10.6%), HPV56 and HPV42 (both 8.8%). No differences were found in terms of clinical and hormonal characteristics between patients with or without seminal HPV. Sperm progressive motility was significantly lower ( P = 0.01) while SDF values were higher ( P = 0.005) in HPV+ men compared to those with no HPV. In particular, HR HPV+ men had lower sperm progressive motility ( P = 0.007) and higher SDF values ( P = 0.003) than those with a negative HPV test. Univariable analysis showed that HR HPV+ was associated with impaired sperm progressive motility ( P = 0.002) and SDF values ( P = 0.003). In the multivariable analysis, age, FSH levels and testicular volume were significantly associated with impaired sperm progressive motility (all P ≤ 0.04). Conversely BMI, CCI, smoking habits and HPV status were not. Only age ( P = 0.02) and FSH ( P = 0.01) were significantly associated with SDF, after accounting for BMI, CCI, testicular volume, smoking habits and HPV status. LIMITATIONS, REASONS FOR CAUTION: Main limitations are the cross-sectional design of our study and the relatively small sample size of the subgroups. Additional limitations are the lack of a control group of normal fertile men and the lack of follow-up testing to check the clearance or the persistence of HPV in semen after a 6–12 months. WIDER IMPLICATIONS OF THE FINDINGS: Overall, these observations point out the importance of an accurate investigation of seminal HPV presence in everyday clinical practice in the diagnostic work-up of infertile men. STUDY FUNDING/COMPETING INTEREST(S): No external funding was used. There are no competing interests.